Simulation and analysis of single-phase grounding fault in small current grounding system. (August 2019) - Fu, Jinwei; Shi, Changkai; Fan, Wenbo; Guan, Shilei
Abstract: The characteristics and distribution of single-phase grounding faults in small current grounding system are not easy to capture, and it is not easy to collect and cover all possible situations in operation site. This paper builds a fault simulation model of distribution network based on PSCAD. By changing the fault location, line type, transition resistance, fault time and other factors, and combining with the analysis of fault mechanism, the factors affecting single-phase grounding faults are obtained. The impacts of fault feature distribution provide theoretical guidance for fault identification equipment function detection and so on.